Cloning and expression of an endoglucanase gene from the thermotolerant fungus Aspergillus fumigatus DBiNU-1 in Kluyveromyces lactis - Rungrattanakasin,Budsayachat (2018)
Abstract An intronless endoglucanase from thermotolerant Aspergillus fumigatus DBINU-1 was cloned, characterized and expressed in the yeast Kluyveromyces lactis. The full-length open reading frame of the endoglucanase gene from A. fumigatus DBiNU-1, designated Cel7, was 1383 nucleotides in length and encoded a protein of 460 amino acid residues. The predicted molecular weight and the isoelectric point of the A. fumigatus Cel7 gene product were 48.19 kDa and 5.03, respectively. A catalytic domain in the N-terminal region and a fungal type cellulose-binding domain/module in the C-terminal region were detected in the predicted polypeptide sequences. Furthermore, a signal peptide with 20 amino acid residues at the N-terminus was also detected in the deduced amino acid sequences of the endoglucanase from A. fumigatus DBiNU-1. The endoglucanase from A. fumigatus DBiNU-1 was successfully expressed in K. lactis, and the purified recombinant enzyme exhibited its maximum activity at pH 5.0 and 60 °C. The enzyme was very stable in a pH range from 4.0 to 8.0 and a temperature range from 30 to 60 °C. These features make it suitable for application in the paper, biofuel, and other chemical production industries that use cellulosic materials.